The Influence of Profitability, Leverage, And Firm Size on Company Value, An Empirical Study of Manufacturing Companies in the Cement Sub-Sector Listed on the IDX in 2016-2023 - Radeva Yudi Mumtaza; Witono, Banu (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of profitability, leverage, and firm size on firm value in cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2016–2023 period. The choice of variables is based on prior research suggesting that profitability reflects a company's ability to generate earnings, leverage illustrates financial risk, and firm size captures resource advantages—each theorized to impact firm value. A quantitative approach was employed, applying multiple linear regression analysis. The regression model was tested for classical assumptions to ensure validity. Sampling was conducted through purposive sampling, targeting companies that consistently published complete financial statements during the study period, resulting in a final sample of [insert number] companies. Secondary data were collected through documentation from the official IDX website. Profitability was measured by Return on Assets (ROA), leverage by Debt to Asset Ratio (DAR), and firm size by the natural logarithm of total assets. Firm value, the dependent variable, was measured using Tobin’s Q, selected for its ability to capture both market perceptions and asset replacement costs, which are particularly relevant for the asset-intensive cement industry. The findings reveal that profitability and firm size do not significantly affect firm value, while leverage has a significant impact.